"I Don't Know What to Say": Teachers' Perspectives on Supporting Bereaved Students After the Death of a Parent. (February 2023) - Levkovich, Inbar; Elyoseph, Zohar
This qualitative study examined teachers' experiences dealing with bereaved students following the death of a parent. The researchers conducted in-depth, semi-structured, face-to-face interviews with 25 teachers in Israeli schools who had counseled one of their students after the death of a parent. The interviews were recorded and transcribed and underwent content analysis. Analysis of the findings revealed that the teachers felt helpless, confused, overloaded emotionally and anxious when counseling students who had lost a parent. In addition, the teachers discussed the complex nature of their relationship with the remaining parent, ranging from a desire to support the family through avoidance for fear of hurting the parent to fears of being overwhelmed by the child's problems. Many teachers mentioned their need for support from school officials.